2005
DOI: 10.2460/ajvr.2005.66.1757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radial shock waves on membrane permeability and viability of chondrocytes and structure of articular cartilage in equine cartilage explants

Abstract: Radial shock waves do not appear to structurally damage articular cartilage but do impact chondrocyte viability and membrane permeability. Caution should be exercised when extremely high periarticular pulse doses are used until additional studies can determine the long-term outcome of these effects and appropriate periarticular treatment regimens can be validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Caution should be exercised when applying these results to the effects of focussed shock waves on cartilage, as focussed and radial shock waves have differing physical properties (Crowe et al 2004;Pauwels et al 2004). However, some cellular effects, such as increases in membrane permeability, have been reported with both focussed shock waves (Zhong et al 1999) and radial shock waves (Byron et al 2005). Unfortunately, studies directly comparing the physical properties of radial and focussed shock waves are scant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Caution should be exercised when applying these results to the effects of focussed shock waves on cartilage, as focussed and radial shock waves have differing physical properties (Crowe et al 2004;Pauwels et al 2004). However, some cellular effects, such as increases in membrane permeability, have been reported with both focussed shock waves (Zhong et al 1999) and radial shock waves (Byron et al 2005). Unfortunately, studies directly comparing the physical properties of radial and focussed shock waves are scant.…”
Section: Discussionmentioning
confidence: 95%
“…Three cartilage explants 6 mm in diameter were arranged concentrically around the centre of the shock-wave fi eld and treated simultaneously for each treatment group. Distal metacarpal and metatarsal cartilage were used in a separate study (Byron et al 2005).…”
Section: Tissue Sources and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…E.g., a recent study demonstrated reduced proteoglycan and collagen type II production by cartilage cells when excessive ultrasound intensities (0.5e0.7 W/cm 2 ) were applied daily for 1 week 125 . While no observed structural damage to articular cartilage was reported in another study 130 , shock waves may increase the permeability of the chondrocyte cell wall and affect their viability 130,131 . Increased cell wall permeability and damage to the tissue matrix can be induced by cavitation 34,132 .…”
Section: Mechano-biological Effects Of Hiumentioning
confidence: 97%
“…The application in the cartilage diseases, as osteoarthritis, is still preliminary. Only a few clinical and experimental researches have studied the effects of the shock waves and the radial waves on chondrocytes and articular cartilage in the human model [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%